Gender transformative approaches: Transforming gender norms to build women’s resilience to the economic impacts of Climate Change in Tanzania’s Fisheries Communities in Muleba - Mudege, Netsayi; Kakwasha, Keagan (WorldFish, 2024)
This intervention description template provides space to document what CGIAR Centers are doing with partners to design and pilot gender transformative interventions in agrifood systems. It contains space to provide details of each gender transformative intervention, including the development challenge(s) that the intervention (and supporting technical interventions) seeks to address, the focus of the intervention, the institutional levels targeted (e.g., family, community, market, state), and expected outcomes, among other relevant information. Each intervention should be documented independently.